Bilateral periprosthetic tibial stress fracture after total knee arthroplasty: A case report. (2016) - Ozdemir, Guzelali; Azboy, Ibrahim; Yilmaz, Baris
Highlights: Periprosthetic tibia fractures are rare cases. Bilateral tibial stress fracture developed after total knee arthroplasty is the first of its kind in the literature. A stress fracture should be kept in mind in the persistent pain in the upper end of the tibia that occurs after surgery. Abstract: Introduction: Periprosthetic fractures around the knee after total knee arthroplasty can be seen in the femur, tibia and patella. The tibial fractures are rare cases. Our case with bilateral tibial stress fracture developed after total knee arthroplasty (TKA) is the first of its kind in the literature. Presentation of case: 75-year-old male patient with bilateral knee osteoarthritis had not benefited from conservative treatment methods previously applied. Left TKA was applied. In the second month postoperatively, periprosthetic tibial fracture was identified and osteosynthesis was implemented with locked tibia proximal plate-screw. Bone union in 12 weeks was observed in his follow-ups. After 15 months of his first operation, TKA was applied to the right knee. Postoperatively in the second month, as in the first operation, periprosthetic tibial fracture was detected. Osteosynthesis with locking plate-screw was applied and union in 12 weeks was observed in his follow-up. He was seen mobilized independently and without support in the last control of the case made in the 24th month after the second operation. Discussion: The number of TKA applications is expected to increase in the future. The incidence of periprosthetic fractures should also be expected to increase in these cases. Periprosthetic tibial fractures after TKA are rarely seen. The treatment of periprosthetic fractures around the knee after TKA can be difficult. Conclusion: In the case of persistent pain in the upper end of the tibia after the surgery, stress fracture should be considered.